Taxonomic revision of Siculodes Guenée and revalidation of Aziba Walker (Lepidoptera, Thyrididae, Siculodinae, Siculodini) - Queiroz-Santos, Luziany; Casagrande, Mirna Martins; Mielke, Olaf Hermann Hendrik (Zootaxa, 2024)
The taxonomy of Siculodes Guenée, 1858 and Aziba Walker, 1865 gen. rev., is revised. A new taxonomic arrangement is proposed for these genera reflecting morphological evidence. Siculodes comprises six valid taxa: S. aurorula Guenée, 1858 (type species), S. avicula Guenée, 1877, S. eurymenana (Walker, 1865), S. satellifera (Gaede, 1936), S. straminula Pagenstecher, 1892, and S. subchalybaea (Walker, 1865) stat. rev.; while Aziba Walker, 1865 gen. rev., since a long time considered a junior synonym of Siculodes is here revalidated and comprises six valid taxa: A. falcata (C. Felder & Rogenhofer, 1875) comb. rev., A. mediula (Guenée, 1877) comb. nov., A. roseobrunneata (Heppner & Thiele, 2017) comb. nov., A. substrigata Warren, 1900 comb. rev., A. transversa Walker, 1865 comb. rev. (type species), and A. vehemensaria (H. Edwards, 1884) stat. rev. et comb. nov. Siculodes serpula Guenée, 1877 syn. reinst. and Risama falcata matusi Köhler, 1940 syn. nov. are considered junior synonymies of A. falcata comb. rev. Lectotypes are designated to Siculodes aurorula Guenée, 1858, Siculodes straminula Pagenstecher, 1892, Aziba falcata (C. Felder & Rogenhofer, 1875), and Risama falcata matusi Köhler, 1940. In addition, all species are redescribed and figured, habitats of some species are reported, and geographical distribution maps are provided for all species.